Procedure of BJB Musisi Credit Program at PT Bank Pembangunan Daerah Jawa Barat dan Banten - Edward Fazri; Siti Maryam (Lembaga Penelitian dan Pengabdian kepada Masyarakat Politeknik Piksi Input Serang, 2022)
Purpose - This study aims to supply an overview of the procedure for applying for BJB Musica credit issued by PT. Regional Development Bank of West Java and Banten Design/method/approach - This study uses a descriptive method, which is a research method based on the philosophy of postpositivism which is used to examine the condition of natural objects. The research was conducted for three months at the Ciruas Branch Office Finding - The BJB Musisi Credit Program is a credit program that is suitable for civil servants who are entering retirement age. The effortless application process and insurance and provision discounts are the main advantages of this product Originality - This study supplies an overview and knowledge about the advantages of BJB Musisis that are useful for civil servants in preparing for retirement